Pendeteksi Kesamaan Dokumen pada Sistem Informasi Pendaftaran Proposal Skripsi dengan Pendekatan Algoritma Rabin-Karp - Pandu Pratama Putra; Afriansyah Afriansyah; Muhammad Syaifullah (INTECOMS: Journal of Information Technology and Computer Science, 2019)
Plagiarism is a significant problem in many areas, including universities. plagiarism is usually performed on digital content is to copy-paste of the original document. To anticipate, we need a way to analyze the technique of plagiarism. There are several approaches that can be taken, for example by using a search algorithm Rabin-Karp string because these algorithms can be used to detect plagiarism in a text document. In the testing phase, the test documents used were three documents with similarity level categories of low, medium and high. From some of the testing that has been done, this approach can find the longest quote the same between the two text documents and measure the similarity of text documents. With this system will help prevent acts of plagiarism in the thesis proposal registration so that the absence of the same thesis. Keywords: Plagiarism, Rabin-Karp algorithm, Similarity, Document